PEMBERDAYAAN MASYARAKAT BERBASIS POTENSI LOKAL MELALUI PENINGKATAN KAPASITAS MANAJEMEN DAN INOVASI PRODUK SEBAGAI UPAYA PENINGKATAN EKONOMI PELAKU USAHA MIKRO DI DESA KALIPANG KECAMATAN GRATI KABUPATEN PASURUAN - Bambang Sutikno; Sri Hastari; Yufenti Oktafiah (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
This community service program aims to increase the capacity of business management and product innovation of cassava chips and tape, so that there is a change from low value to competitive superior products with high economic value. The implementation method is by training and mentoring (1) empowering business management capacity, (2) empowering product innovation, (3) empowering financial bookkeeping, (4) empowering marketing methods. This activity involves micro business partners in Kalipang Village whose business only focuses on cassava chips and tape. The results of these training and mentoring activities indicate that there is knowledge empowerment on business management capacity; motivation to innovate; understand financial and marketing reports as well as empowerment occurs about the importance of having a business license which in turn can help improve the economy and improve the quality of life of micro business managers in a sustainable manner.